Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Terumbu Karang Melalui Proses Presipitasi Dengan Variasi Rasio Ca/P Dan pH Reaksi - Getra Anugrah; Yelmida Azis; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite is a crystalline molecule composed of phosphorus and calcium with the molecular formula Ca10(PO4)6(OH)2. Synthetic hydroxyapatite is known as one of the important implant materials because it has bioactive, biocompatible and osteoconductive properties that chemically resemble bone and tooth mineral components, so it can be used as a substitute for human hard tissue. In this study hydroxyapatite was synthesized from PCC coral reefs using precipitation method with variations in pH (9; 10 and 11) and the mole ratio of Ca/P (1.57; 1.67 and 1.77). The obtained hydroxyapatite was analyzed by using XRD and SEM-EDX analysis. The obtained hydroxyapatite obtained was analyzed by XRD analysis with the best crystallinity closest to the standard hydroxyapatite and the smallest crystal sized was 10.76507 nm at pH 9 with Ca/P ratio of 1.67. Based on the SEM-EDX analysis, the best results was produce at pH 9 and the mole ratio of Ca/P 1.67 with agglomerate shaped particles, 2.549% particle distribution and final Ca/P mole ratio 1.61.Key word: Ca/P ratio, hydroxyapatite, pH, precipitation